Non-Circular Journal Bearings - Chauhan, Amit.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This brief details non-circular journal bearing configurations. The author describes the mathematical and experimental studies that pertain to non-circular journal bearing profiles and how they can be applied to other types of bearing profiles with some modifications. He also examines non-circular journal bearing classifications, the methodology needed to carry out mathematical modeling, and the experimental procedures used to determine oil-film temperature and pressures.
Introduction -- Classification of Non-circular Journal Bearings -- Performance parameters -- Definitions -- Mathematical Analysis -- Experimental Procedure -- Present status of thermal effects in Non-circular bearing -- Summary and Future.
Keywords: Coatings; Tribology; Corrosion and anti-corrosives.; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Coatings; Tribology; Corrosion; Engineering Thermodynamics, Heat and Mass Transfer; Thermodynamics